The Left in China : A Political Cartography. - Ruckus, Ralf. (London : Pluto Press, 2023)
A timely, ambitious and unique book that traces the history and present state of leftist politics in China.
Cover -- Title -- Copyright -- Contents -- List of Figures and Tables -- Abbreviations -- Preface -- Acknowledgments -- 1 Introduction: Understanding the Left in the People's Republic -- Initial Questions and Perspectives -- The Making of the (Global) Left -- Visualizing the Composition of the Left -- Early History of the Chinese Left -- Structure of the Book -- 2 Against Broken Promises: Workers Claim Equality and Participation in the Socialist 1950s and 1960s -- Workers' Struggles and Political Discontent 1956-57 -- Economism and the Rebel Movement 1966-68 -- Conclusion: Regime Betrayal and Class Resistance -- 3 For a Better Future: Worker Movements Demand Democratic Reforms in the 1970s and 1980s -- The April 5 Movement 1976 -- The Democracy Wall Movement 1978-80 -- Workers in the Tian'anmen Square Movement 1989 -- Conclusion: Movements For and Against the Reforms -- 4 Defense and Nostalgia: Social Struggles Drive Leftist Resistance in the 1990s and 2000s -- Peasant Struggles Against Reform Effects -- State Workers Against Smashing the Iron Rice-bowl -- Maoist Organizing and the New Left -- Conclusion: Old Class Composition, New Leftist Mobilization -- 5 Social Unrest and Organizing: Challenges for the CCP in the Capitalist 2000s and 2010s -- The New Working Class -- The Recomposed Left -- Women*'s Struggles Against Patriarchal Regimes -- Feminists (Not) Challenging the Party State -- Conclusion: Struggles Force the Regime to Adapt -- 6 Conclusions: Social Discontent and Left Opposition in Socialism and Capitalism -- How Social Unrest and the Left Changed Since 1949 -- Dynamics of Struggles and Countermeasures -- Visualizing the PRC's (Other) Left -- The CCP's Anti-leftist Record -- Lessons for Left-wing Strategies -- Epilogue -- Chinese Terms and Characters -- Notes -- Works Cited -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: China-Politics and government-1949-.; Electronic books